La chorégraphe qui décolonise la danse. Gymnastique, la culture en s'amusant - Dembélé, Bintou (2021)
En 2019, à Bastille, on assiste à la représentation des "Indes galantes", l’ode à l’exotisme colonial de Rameau, revisitée par Clément Cogitore dans une version hip-hop ! Qui est derrière cette révolution ? Bintou Dembélé, première femme noire à avoir chorégraphié un ballet à l’opéra de Paris en trois cent cinquante ans. Programme court (2020, 6mn) Disponible jusqu'au 10/01/2026
Keywords: antiracisme; approches et analyses; arts; cours; danse; discipline; discours dominant; fem3100; militance; premier cycle; ressource en ligne; systèmes d'oppressions; thématiques

“Just a couple of queer fish”: The queer possibilities of Rita Mae Brown’s Rubyfruit Jungle - Lorig, Josette (Contemporary Women's Writing, 2021)
Rita Mae Brown’s Rubyfruit Jungle (1973) is a foundational work of lesbian literature and has been characterized as a queer text. This essay begins with resistance to reading the novel as a wholly celebratory queer text because of how it positions a form of essentialized lesbianism against queer sexualities that are coded as deviant and abnormal. Nonetheless, Rubyfruit Jungle brims with queer narratives, queer scenes, and queer characters. In the essay’s second half, I draw on Eve Kosofsky Sedgwick’s model of reparative reading to engage with potential queer readings the novel affords. I show how readers can recuperate the queer sexualities the novel documents in ways that the novel – with its specific historical and political positionality – did not or could not account for.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; identités LGBTQIA2+; personnes lesbiennes; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires